Ten years of pediatric surgery in a secondary level perinatal hospital in Mexico - Gerardo Fernández-Ortega; Gabriela C. Morón-García; Lidia E. García-Sosa; María S. Suárez-Delgadillo; Alejandro Hinojosa-Velasco (Permanyer, 2023)
Background: Neonatal surgery is one of the most specialized and demanding areas of pediatric surgery due to the specific anatomical and physiological characteristics of this vulnerable group of patients. This study aimed to present the experience of 10 years of neonatal surgical management in a secondary care perinatal hospital in Mexico. Methods: We conducted a descriptive, observational, cross-sectional, and retrospective study in a perinatal hospital in Toluca, Mexico, from August 01, 2012, to July 31, 2022. We included patients who underwent surgery within the hospital facilities by the Service of Pediatric Surgery. We studied demographic, clinical, and surgical variables and performed descriptive and inferential statistics. Results: A total of 551 patients underwent surgery during this period with a prevalence of 0.5%. The number of patients operated in the neonatal period was 497 (90.1%). Forty-eight pathologies were recorded, with a predominance of congenital malformations in 64.6% and prenatal diagnosis in 40.5% of cases. The survival rate was 89.7%. In the bivariate analysis of mortality, we found an inverse relationship between weight and gestational age (p < 0.05). Conclusion: Although not a local or national reference center, the hospital where the study was conducted treats various congenital and acquired diseases, with a mortality rate that tends to decrease, close to the international average, and lower than national reports.